Identification and characterization of Fusarium mangiferae as pathogen of mango malformation in India - Kumar,Pradeep (2016)
ABSTRACT Fusarium mangiferae (=F. subglutinans) isolates collect from malformed samples from major mango-growing area of North India. Molecular identification and characterization of eleven most virulent isolates of F. mangiferae, based on pathogenicity tests used for the present study. Species-specific, genus specific ITS-PCR and PCR-RFLP performed for the accurate and easy detection of F. mangiferae. The rDNA-ITS 28S region sequences used for phylogenetic analysis of Fusarium isolates from India and other countries for homology search between them. The phylogenetic tree divided the isolates into three clades (i.e., American, Asian and African) and showed the high level of sequence based similarity (69-99%) among all Fusarium sequences from Asia. Thus, claimed Fusarium mangiferae as dominant pathogen of mango malformation. Furthermore, we conclude that exploiting the nested PCR coupled with PCR-RFLP will help in rapid and accurate detection of F. mangiferae pathogen of mango malformation.